Translation of nominal beta clause functions as a subject in Hemingways the old man and the sea from English into Arabic - Hamood, Muhammed Ibrahim; Md Rashid, Sabariah; Syed Abdullah, Syed Nurulakla; Ismail, Muhd Zulkifli (Malaysian Translators' Association, 2018)
This paper reports on a study that focuses on the translation of beta clause functions as a subject from English into Arabic. Specifically, it aimed to examine the extent to which the English nominal beta clause functions as a subject functions in Hemingway’s novel The Old Man and the Sea in the Arabic translation by Ali Al-Qasimi have been preserved. This study uses a qualitative descriptive method. The source of data is English novel, Hemingway’s "The Old Man and the Sea" and its translation in Arabic translation done by Ali Al-Qasimi (2008). The study adopted Halliday’s Functional Grammar (2014) as a model for analysing the English nominal beta clause functions as a subject functions and. The study adopted two theories, namely, Halliday’s theory of functional grammar and Newmark's theory of semantic and communicative translation in Arabic translation as a model of analysing and testing the meaning of the English nominal beta clause in Hemingway’s The Old Man and the Sea into Arabic translation. The findings obtained revealed that the nominal beta clause functions as a subject were translated differently into the TT. Specifically, the nominal beta clause functions as a subject has been rendered into different structures such as group, alpha clause, beta clause but having different functions and complex clause.